BETWEEN ISLAMIC LAW AND HUMAN RIGHTS: AMBIGUOUS REGULATION REGARDING POLYGAMY IN INDONESIA - Basuki Kurniawan; Edi Purwanto; Sareef Tehtae (UIN Kiai Haji Achmad Siddiq Jember, 2022)
Indonesia's polygamy regulations, which allow men to practice polygamy and prohibit women from practicing polygamy, have the potential to violate human rights. Suppose the study of the theory of state responsibility, the assertion of gender equality must be supported in all aspects of life, especially in marriage. Indonesia has also ratified CEDAW as a national law that can be used as a guide. Therefore, the ratification of CEDAW has significant implications for Indonesia, which will immediately revise the polygamy requirements in the marriage law to prevent discrimination from continuing. It is because delaying the protection of human rights also means that the state cannot protect and respect women's rights and is considered reckless. Therefore, state delays can be viewed as a violation of human rights.